El problema de la identidad narrativa en la filosofía de Paul Ricoeur - Néspolo, Jimena (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2007)
This article analyses the í¹narrative identityí¹ problem as a nodal point in the development of Paul Ricoeurïs philosophy. In clear opposition to í¹cogitum philosophiesí¹ in which the self is defined as í¹empirical selfí¹ or as í¹transcendental selfí¹, the French philosopher proposes the oneself as another concept by bringing together selfness and ipseity notions into a single center to which the individual can access only through a narrative turn denominated í¹yes hermeneuticsí¹. To comprehend the notion of subject outlined by this philosophical concept will be our aim.